The missus - James, E. L. (Mister & missus, 2023)
"Maxim Trevelyan, reluctant Earl of Trevethick, has pursued the woman he loves to the wilds of Albania. Having fought for and won her, he now has to wed her, at the sharp end of a shotgun. But can a reformed rake like Maxim ever make a good husband -- or will his own notorious reputation and the scandalous secrets of his aristocratic family destroy his newfound happiness? Alessia Demachi has defied and outwitted kidnappers and traffickers, and won the heart of the man she loves, but can she make this marriage work? Confronted by Maxim's lurid past, his forbidding family, and the looks and whispers of London's elite, will she ever be seen as Maxim's countess -- or will she always be his former cleaner?"--Amazon.